Food consumption and depression among Brazilian adults: results from the Brazilian National Health Survey, 2013 - Kamilla Tavares de Sousa; Emanuele Souza Marques; Renata Bertazzi Levy; Catarina Machado Azeredo
Abstract: Our study aimed to evaluate the association between food consumption and depression. We used data from the Brazilian National Health Survey; a cross-sectional study carried out in 2013 among 46,785 Brazilian adults. The exposures were regular consumption (≥ 5 times/week) of the markers of healthy (beans, vegetables, fruits, and natural fruit juices) and unhealthy food (sugar sweetened beverages; sweets and the substitution of lunch or dinner for snacks); and a nutritional score elaborated by combining the frequency of consumption of markers of healthy and unhealthy food, the higher the value, the better the diet. The outcome was depression, assessed through the PHQ-9 questionnaire answered by the participants. Those with PHQ-9 scores greater than or equal to 10 were classified as presenting depression. We performed logistic regression models adjusted for potential confounders. Regular consumption of sweets (OR = 1.53; 95%CI: 1.33-1.76) and regular replacement of meals for snacks (OR = 1.52; 95%CI: 1.21-1.90) were positively associated with depression. Regular consumption of sugar sweetened beverages was positively associated with depression among women (OR = 1.27; 95%CI: 1.10-1.48). Regular consumption of beans was negatively associated with depression (OR = 0.74; 95%CI: 0.65-0.84), consistent for both sexes. Comparing the top quintile of the nutritional score (healthier diet) to the bottom quintile (less healthy) we found a negative association with depression (OR = 0.63; 95%CI: 0.52-0.75). Our results add evidence on a possible role of food consumption in depression; future longitudinal studies should explore the mechanisms of these associations.